Evaluation of in vitro testing strategies for hazard assessment of the skin sensitization potential of "real‐life" mixtures: The case of henna‐based hair‐colouring products containing p‐phenylenediamine. (20th June 2019) - de Ávila, Renato Ivan; Veloso, Danillo F. M. C.; Teixeira, Gabriel C.; Rodrigues, Thaisângela L.; Lindberg, Tim; Lindstedt, Malin; Fonseca, Simone G.; Lima, Eliana M.; Valadares, Marize C.
Abstract: Background: Allergic contact dermatitis caused by henna‐based hair‐colouring products has been associated with adulteration of henna with p ‐phenylenediamine (PPD). Objectives: To develop a testing approach based on in vitro techniques that address key events within the skin sensitization adverse outcome pathway in order to evaluate the allergenic potential of hair‐colouring products. Methods: The following in vitro assays were used to test the sensitizing capacity of hair dye ingredients: the micro‐direct peptide reactivity assay (mDPRA); the HaCaT keratinocyte‐associated interleukin (IL)‐18 assay; the U937 cell line activation test (U‐SENS)/IL‐8 levels; the blood monocyte‐derived dendritic cell test; and genomic allergen rapid detection (GARD skin). Those techniques with better human concordance were selected to evaluate the allergenic potential of 10 hair‐colouring products. Results: In contrast to the information on the label, chromatographic analyses identified PPD in all products. The main henna biomarker, lawsone, was not detected in one of the 10 products. Among the techniques evaluated by testing hair dye ingredients, the mDPRA, the IL‐18 assay, GARD skin and the U‐SENS correlated better with human classification (concordances of 91.7%‐100%) and were superior to the animal testing (concordance of 78.5%). Thus, these assays were used to evaluate hair‐colouring products, which were classified as skin sensitizers by the use of different two‐of‐three approaches. Conclusions: Our findings highlight the toxicological consequences of, and risks associated with, the undisclosed use of PPD in henna‐based "natural" "real‐life" products.